Time-frequency analysis of intermittent two-phase flows in horizontal piping - Klein,F. L. (2004)
One of the main features associated to multiphase flows is the existence of characteristic dynamic structures according to which the different phases of a mixture of immiscible fluids can flow. The manifestation of one of these structures, known as flow pattern or regime, is determined by the flow rates as well as by physical and geometrical properties of the fluids and piping. The development of flow pattern characterization and diagnostic methods, and the associated transitions in between, is of crucial importance for an efficient engineering of such phenomena. Time-frequency analysis is used in this work to characterize horizontal air-water intermittent flow regimes. More specifically, our main objective is to reveal the existence of sub-regimes inside the intermittent regimes region with the help of the corresponding time-frequency covariance, which is capable of detecting transitions by assessing the unstationarity associated with the corresponding transitions. Experimental tests were conducted at the TALC facility at CEA-Grenoble and an extensive database was obtained, covering several types of intermittent flow. A conductivity probe, consisting in two ring electrodes flush mounted to the pipe, delivered signals from which the time-frequency covariance was calculated from the corresponding Gabor transform.